Experiences of Mapuche women in Olavarría. An ethnographic approach to multiple ontologies - Lencina, Rocio (2021)
Introduction This article presents advances of the doctoral thesis in Anthropology, research that considers the city of Olavarría (Buenos Aires, Argentina) as a study area where women who assume an indigenous identity (Mapuche) live and who are developing, as such, a active role in the community. Main objective In this framework, the main objective is to understand how Mapuche women appropriate, re-signify, value the ancestral cultural legacy, recovering their experiences (past and current) around the Mapuche worldview. Method and technique This study is based on a qualitative approach from an ethnographic perspective, based on techniques such as the interview and participant observation, as well as the survey and analysis of documentary sources. Results Certain aspects of the ancestral cultural legacy related to ritual practices expressed in ceremonies and daily events are recovered to think about them from the ontological dimension of the sociocultural processes retaken by the interviewees. The main results allow us to reflect on circularity as a principle (spatial and temporal) and symbolism, the role of ceremonial and ritual practices for daily life and its re-signification in an urban context, the centrality of the link with the forces of the nature, among others. [Continue reading in the article]